2005
DOI: 10.1177/003335490512000509
|View full text |Cite
|
Sign up to set email alerts
|

Enrollment of Racial/Ethnic Minorities in NIAID-Funded Networks of HIV Vaccine Trials in the United States, 1988 to 2002

Abstract: Objective. The purpose of this study was to analyze enrollment of racial/ethnic minorities in Phase I and Phase II HIV vaccine trials in the U.S. conducted by National Institute of Allergy and Infectious Diseases (NIAID)-funded networks from 1988 to 2002. Methods. A centralized database was searched for all NIAID-funded networks of HIV vaccine trial enrollment data in the U.S. from 1988 through 2002. The authors reviewed data from Phase I or Phase II preventive HIV vaccine trials that included HIV-1 uninfected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 20 publications
1
29
1
Order By: Relevance
“…Unless measures are taken to increase Hispanic American enrollment, the magnitude of underrepresentation will likely increase as the Hispanic population is rapidly growing; Hispanic Americans are estimated to make up 16% of the US population in 2010 and 19% by 2020. 17 The discordance between Hispanic American underrepresentation and African American overrepresentation in our series has not been reported in disease-specific series, 11,25 but is consistent with the overall trend in NIH trial enrollment. 10 There are several potential explanations.…”
Section: Sensitivity Analysissupporting
confidence: 86%
See 2 more Smart Citations
“…Unless measures are taken to increase Hispanic American enrollment, the magnitude of underrepresentation will likely increase as the Hispanic population is rapidly growing; Hispanic Americans are estimated to make up 16% of the US population in 2010 and 19% by 2020. 17 The discordance between Hispanic American underrepresentation and African American overrepresentation in our series has not been reported in disease-specific series, 11,25 but is consistent with the overall trend in NIH trial enrollment. 10 There are several potential explanations.…”
Section: Sensitivity Analysissupporting
confidence: 86%
“…24 Despite this willingness to participate, underrepresentation of Hispanic Americans has been repeatedly documented. 9,11,25 Several hypotheses have been postulated to explain this phenomenon. 11,26 For example, language barriers, 27 potential concerns about documentation status, 28 and the geographic distribution of trial enrollment sites relative to the Hispanic American population 29 may be issues in this subgroup.…”
Section: Sensitivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] For example, the AIDSVAX B/B study, which included relatively small numbers of minority participants, suggested that vaccine efficacy rates were higher among Black and Asian participants; however, this subgroup analysis was inconclusive. 6,7 The racial/ethnic disparities in the epidemiology of HIV are also a justification for increased enrollment of minorities in HIV vaccine trials, as the US Food and Drug Administration (FDA) desires adequate representation of race/ethnicity in evaluation of new products (Dr Jared Baeten, personal communication). However, in one meta-analysis of hypothetical HIV vaccine acceptiblity in the US, being Black/African-American (in reference to White) was negatively associated with HIV vaccine acceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…2 While development of an effective vaccine has remained elusive, medical treatment for HIV/AIDS has burgeoned, and heightened attention is being paid to factors affecting participation in treatment-related clinical trials and behavioral research. In addition, recognition of an under-representation of minorities in clinical trials disproportionate to the disease burden of minority populations [3][4][5] has led to increasing numbers of studies to understand motivations for participating in HIV-related research across diverse populations.…”
Section: Introductionmentioning
confidence: 99%